2014
DOI: 10.5935/1678-9741.20140076
|View full text |Cite
|
Sign up to set email alerts
|

Indication of endovascular treatment of type B aortic dissection - Literature Review

Abstract: Aortic dissection is a cardiovascular event of high mortality if not early diagnosed and properly treated. In Stanford type A aortic dissection, there is the involvement of the ascending aorta, whereas in type B the ascending aorta is not affected. The treatment of type A aortic dissection is mainly surgical. The hospital mortality of type B aortic dissection surgical treatment is approximately 20%, while medical therapy is 10%. However, half the patients who are discharged from hospital after medical treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…15 Open vascular reconstruction mortality in patients with vEDS is 20-65% while mortality associated with arteriography in this population is 17%-67%, 16 highlighting the importance of developing targeted approaches for complicated cases. Endovascular repair has emerged as the preferred technique for uncomplicated and complicated Type B or DeBakey Type III aortic dissection, [17][18][19] but such interventions for EDS patients is still debatable. [12][13][14] Given that EDS can contribute to medial degeneration and consequential intimal tears, acute dissection pathophysiology is similar to that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…15 Open vascular reconstruction mortality in patients with vEDS is 20-65% while mortality associated with arteriography in this population is 17%-67%, 16 highlighting the importance of developing targeted approaches for complicated cases. Endovascular repair has emerged as the preferred technique for uncomplicated and complicated Type B or DeBakey Type III aortic dissection, [17][18][19] but such interventions for EDS patients is still debatable. [12][13][14] Given that EDS can contribute to medial degeneration and consequential intimal tears, acute dissection pathophysiology is similar to that of the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a mortality rate of < 10% and > 80% success rate of occlusion and thrombosis of the false lumen with EVR. 22 The establishment of the International Registry of Acute Aortic Dissection (IRAD) in 1996, which gathers information from 24 centers in 11 countries, has helped in the development of an understanding of the complexity of AD. 3 At present, the AD-referral centers routinely advocate EVR for complicated type B dissection, as acceptable early and midterm results have shown that there is adequate prevention of aneurysm rupture.…”
Section: Treatmentmentioning
confidence: 99%